Polymorphisms in DENND1B gene are associated with asthma and atopy phenotypes in Brazilian children - Fiuza, Bianca Sampaio Dotto (2017)
CNPq − National Research Council - Brazil and FAPESB − State of Bahia, Brazil Research Council